2015
DOI: 10.1080/15389588.2015.1023896
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Red Light Cameras on Crashes Within Miami–Dade County, Florida

Abstract: RLCs showed a benefit in reducing RLR-related injury collisions at camera sites after enforcement commenced, yet its tradeoff was a large increase in rear-end collisions. There was inconclusive evidence whether RLCs affected right angle/turning and all injury collisions. Statutory changes in crash reporting during the second year of camera enforcement affected the incidence of right angle and rear-end collisions; nevertheless, a "novelty effect" could not be ruled out. Future research should consider events su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…These interventions share a common focus on risky driving behaviors, together with driver capacity and training. This review found the most effective interventions were mandatory seat belts (3336), antilock brake systems (37), camera speed control (3840), helmet use by motorcycle drivers (36), and graduated driver licensing for new drivers (27, 4144). Several studies assessed graduated driver licensing in the United States, both federally and in states, and showed that implementation of this program reduced accidents in young, inexperienced drivers by 19% – 39% (27).…”
Section: Resultsmentioning
confidence: 99%
“…These interventions share a common focus on risky driving behaviors, together with driver capacity and training. This review found the most effective interventions were mandatory seat belts (3336), antilock brake systems (37), camera speed control (3840), helmet use by motorcycle drivers (36), and graduated driver licensing for new drivers (27, 4144). Several studies assessed graduated driver licensing in the United States, both federally and in states, and showed that implementation of this program reduced accidents in young, inexperienced drivers by 19% – 39% (27).…”
Section: Resultsmentioning
confidence: 99%
“…There is no unique pathway linking mechanical loading to bone (re)modeling; rather, multiple pathways that are responsive to various signals, including mechanical strain, participate in the adaptive response [6]. Currently, the Wnt/β-catenin signaling pathway is viewed as a dominant pathway in adaptation to mechanical loading [5, 711]. Osteocytes regulate Wnt/β-catenin signaling via secretion of sclerostin, which antagonizes Wnt signaling by binding low-density lipoprotein receptor-related protein-5 and -6 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Scarce research can be found about this type of TCM. Normally, papers focus on traffic offenses involving red lights and on the effectiveness of red light cameras on accidents (Baratian-Ghorghi, Zhou, and Zech, 2016;Llau, Ahmed, Khan, Cevallos, and Pekovic, 2015;Jensupakarn and Kanitpong, 2018), but the efficiency of the traffic lights used for this research is not analyzed as a TCM in the literature.…”
Section: Introductionmentioning
confidence: 99%